Mathematical Representation Ability Viewed from Students' Self-Concept in Class VII Quadrilateral Material - Sari, Rahastri Pundhi; Waluya, St. Budi; Supriyadi, Supriyadi (Educational Management, 2021)
The ability of mathematical representation and self-concept is important for students to understand mathematics in life and the effective ability of students in learning. This study aims to analyze students' mathematical representation abilities in terms of high, medium and low self-concepts. This study used a qualitative method. Grounded theory type design. The research subjects were grade VII students of SMP Negeri 3 Pati. Based on the results of the study, it was found that students' mathematical representation abilities in terms of their high self-concept never gave up to always try to solve problems with the right steps. Students who have their own concept who think that failure is due to trying, not because of their limited abilities, they still believe that if they want to try they can definitely solve existing problems. In addition, students who have good mathematical self-concepts can also make their mathematical abilities better. Representative abilities of students seen from self-concept who have confidence in their abilities, but sometimes give up when solving problems with difficult questions. They have enthusiasm in solving existing problems even though there are still mistakes. The ability of student representation in terms of low self-concept, students who are included in the category of low self-concept do not have confidence in their abilities, they easily give up when solving problems that approach difficult ones.